Finding Herself Alone: Emily Dickinson, Victorian Women Novelists, and the Female Subject - Mayer, Nancy (Romanticism on the Net, 2005)
AbstractAnglo-American Romanticism, beginning with Wordsworth and then beginning again with Emerson, is, in large part, a long conversation about subjectivity, especially about how to reconcile a pure "transparent" perceptive power of the poetic imagination with the recognition of other subjectivities and the limitations of one's own identity. It is a conversation that most critics have assumed excluded women writers. As a lyric poet whose subject is subjectivity, Emily Dickinson has been the intermittent exception to this rule as, in years past, the only recognized female participant in literary American Romanticism. The speculative interiority of her work does, in fact, set her apart from her countrywomen, but not from the English women writers she extravagantly admired. In placing Dickinson's poem alongside the novels of the Victorian British women novelists, I find a common interest in the existential problem of subjectivity, with central characters who could be Dickinson's lyric subject, but placed more firmly in a social setting and within the constraints of gender. I maintain that in Dickinson's poems, as in the novels of Charlotte Brontë, George Eliot, and Emily Brontë, there is a conscious ethical engagement with the opposition between the possibilities of Romantic transcendence and the necessity of respecting the limits that define us. Although their ethical perspectives are different, each of these late Romantic women writers re-examines what it means to be a self alone.